Edukasi Hukum Tentang Pemahaman Perkawinan Pada Siswa SMA Negeri 4 Palu - Andi Bustamin Dg. Kunu; Muhammad Ayub Mubarak; Manga Patila; Mohammad Saleh; Irzha Friskanov. S (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
Marriage is a legal bond that has profound social, economic, and psychological consequences. In Indonesia, Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 has regulated the minimum age of marriage, which is 19 years for men and women. However, in reality, there are still many children and adolescents who do not understand the legal provisions of marriage and the impact it causes, especially related to the risks of early marriage. This community service activity was carried out at SMA Negeri 4 Palu by involving participants from student council members. Using the method of presentation of the material and the discussion method, this activity provides legal education to children and adolescents about the understanding of marriage, their rights, and the legal consequences of early marriage. The lack of legal literacy among children and adolescents makes them vulnerable to marriages that do not conform to the rule of law, which can negatively impact their education, health, and future. Through this program, it is hoped that participants will have a better understanding of marriage law and be able to make wiser decisions in planning their future. In addition, the involvement of various parties such as schools, families, and the community in this program is expected to create a more supportive environment for the protection of children's rights and the prevention of early marriage in Indonesia.